Impact of CD34+ stem cell dose on engraftment period in allogeneic peripheral blood stem cell transplanted patients - Suria Abdul Aziz,; Hazlina Diyana B,; Zed Zakari AH,; Nurasyikin Y,; Yousuf R,; Azma RZ, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Haematopoietic progenitor stem cells acquired from the peripheral blood have been increasingly used to treat patient with haematological malignancy. The success of the allogeneic peripheral blood stem cell transplantation (PBSCT) is significantly dependent on amount of CD34+ stem cell infused which will determine the rate of the haematopoietic recovery and engraftment. This study was aimed to correlate the amount of CD34+ cell infused with the period of engraftment. This retrospective study was conducted on 62 patients with haematopoietic malignancy who have received PBSCT at Universiti Kebangsaan Malaysia Medical Centre from year 2011 to 2015. The impact of CD34+ stem cell infusion on neutrophil and platelet engraftment and obtaining complete chimerism was studied. Patients were divided into two groups based on the amount of CD34+ stem cell. Group A consisted of 9 patients and infused with <5x106 cells/kg CD34+ cell while Group B consisted of 53 patients and infused with ≥5x106 cells/kg CD34+ stem cell. Data were collected and analysed. Group B patients were significantly associated with faster neutrophil engraftment: 12 (10-14) days while group A were 15 (10-21) days, (p=0.002). Platelet engraftment was also faster in group B: 17(12-25) days compared to group A: 18 (15-30) days. Complete chimerism in group B occurred in 30 (15-90) days and in group A was 60 (30-240) days. Platelet engraftment (p=0.149) and complete chimerism (p=0.021) were not significantly influenced by the CD34+ cell count. This study has shown that infusion of ≥5x106 cells/kg CD34+ stem cell shorten the time to haematopoietic engraftment particularly of neutrophilic engraftment.